Exanthem Subitum CNS Complications - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
Central nervous system (CNS) complications of exanthem subitum were analyzed in 21 infants examined at the Departments of Pediatrics and Neurology, Fujita Health University School of Medicine, Toyoake, Japan.